Text Messaging: An Emerging Marketing Tool - Gopal, K. Giridhar (Indian Journal of Marketing, 2007)
Text Messaging also known as SMS (Short Message Service), allows users to type short text messages in order to be displayed and received on the mobile phone. Additionally, the 2-Way Text Messaging, which is also known as MO-SMS (Mobile-Originated Short Message Service), allows messages to be sent through the phone. Messages can be sent from one phone to another by addressing the message to the recipient's phone number. In addition, messages can also be sent to phone via special email address, carrier's website or special messaging software. Moreover, majority of phones and carriers today allow users to send messages directly to an email address. Text messaging refers to sending short text messages from a mobile phone to other mobile phone users using the SMS standard.